Correlations among pain, depressive symptoms, constipation, and serotonin levels in smokers and non smokers. Issue 4 (23rd March 2020) - Lee, Eun Jin
Abstract: Purpose: To examine the differences and correlations among pain, depressive symptoms, and constipation in smokers and non smokers. Design and Methods: The present study was a cross‐sectional study that used descriptive correlations. This study was a secondary analysis of a randomized clinical trial. Findings: Smokers had more pain, depressive symptoms, and constipation than non smokers. Smokers had similar serotonin levels compared with non smokers. Positive correlations were observed between constipation and serum serotonin levels ( r  = .19, P  = .039, n = 116), between constipation and depressive symptoms ( r  = .18, P  = .023, n = 164), and between constipation and pain ( r  = .23, P  = .004, n = 164) in smokers. Practical Implications: Health professionals should assess and treat patients with the knowledge that the severity of pain, depression, and constipation may be greater in smokers than in non smokers.